Kreativitas Guru Dalam Meningkatkan Motivasi Belajar Peserta Didik Melalui Strategi Blended Learning Pada Mata Pelajaran IPS - Shafadella Hendrina (PAKIS (Publikasi Berkala Pendidikan Ilmu Sosial), 2023)
Fostering students' creativity through education has become increasingly crucial in the 21st century. This era demands that educators actively nurture creativity in students across all subjects. Notably, teachers play a pivotal role in enhancing students' creativity, even within the context of social studies during the transitional period of the Covid-19 pandemic. This study has two primary objectives. Firstly, it seeks to elucidate how teachers at MTS Negeri 6 Jakarta employ creativity to bolster student motivation through blended learning strategies. Secondly, it endeavors to identify the obstacles encountered during the use of blended learning in the context of social studies amid the COVID-19 pandemic transition. The research employs a qualitative approach with a descriptive method. Data collection methods encompass observations and interviews involving social studies teachers and students. The findings of this study are as follows: Firstly, the majority of students have adeptly adapted to the learning processes facilitated by teachers through blended learning during the COVID-19 pandemic transition. They exhibit active engagement in learning through activities on platforms like WhatsApp groups, Google Classroom, and Google Meet's question-and-answer sessions. Secondly, the main hindrance to effective blended learning is the insufficient availability of adequate learning facilities.